Lactoferrin infant feeding trial_Canada (LIFT_Canada): protocol for a randomized trial of adding lactoferrin to feeds of very-low-birth-weight preterm infants - Elizabeth V. Asztalos; Keith Barrington; Abhay Lodha; William Tarnow-Mordi; Andrew Martin (BMC, 2020)
Abstract Background In Canada alone, almost 3000 VLBW infants are born and treated annually with almost 1200 going onto death or survival with severe brain injury, chronic lung disorders, aggressive retinopathy of prematurity, late-onset sepsis, or significant necrotizing enterocolitis. Lactoferrin is an antimicrobial, antioxidant, anti-inflammatory iron-carrying, bifidogenic glycoprotein found in all vertebrates and in mammalian milk, leukocytes and exocrine secretions. Lactoferrin aids in creating an environment for growth of beneficial bacteria in the gut, thus reducing colonization with pathogenic bacteria. It is hypothesized that oral bovine lactoferrin (bLF), through its antimicrobial, antioxidant and anti-inflammatory properties, will reduce the rate of mortality or major morbidity in very low birth weight preterm infants. Method Lactoferrin Infant Feeding Trial_Canada (LIFT_Canada) is a multi-centre, double-masked, randomized controlled trial with the aim to enroll 500 infants whose data will be combined with the data of the 1542 infants enrolled from Lactoferrin Infant Feeding Trial_Australia/New Zealand (LIFT_ANZ) in a pooled intention-to-treat analysis. Eligible infants will be randomized and allocated to one of two treatment groups: 1) a daily dose of 200 mg/kg bLF in breast/donor human milk or formula milk until 34 weeks corrected gestation or for a minimum of 2 weeks, whichever is longer, or until discharge home or transfer, if earlier; 2) no bLF with daily feeds. The primary outcome will be determined at 36 weeks corrected gestation for the presence of neonatal morbidity and at discharge for survival and treated retinopathy of prematurity. The duration of the trial is expected to be 36 months. Discussion Currently, there continues to be no clear answer related to the benefit of bLF in reducing mortality or any or all of the significant neonatal morbidities in very low birth weight infants. LIFT_Canada is designed with the hope that the pooled results from Australia, New Zealand, and Canada may help to clarify the situation. Trial registration Clinical Trials.Gov, Identifier: NCT03367013, Registered December 8, 2017.